Application of COLREGs in Close-Quarters Situations: A Study of Deck Officer Decision-Making Competency and Procedural Knowledge Among Indonesian Seafarers - Titis Ari Wibowo; April Gunawan Malau; Meilinasari Nurhasanah Hutagaol (International Forum of Researchers and Lecturers, 2026)
The International Regulations for Preventing Collisions at Sea govern every navigational encounter between vessels, yet the quality of deck officers' procedural knowledge and decision-making competency in applying these regulations under the dynamic, time-pressured conditions of close-quarters situations represents a critical and empirically underexamined dimension of maritime navigational safety. This study investigates the quality and consistency of COLREGs application competency among Indonesian deck officers through a qualitative design combining scenario-based knowledge assessment vignettes with structured interviews and focus group discussion. Data were collected between April 2025 and April 2026 from twenty-four participants comprising active deck officers serving as chief mates and second officers, STIP Jakarta Nautika lecturers, and maritime casualty investigation specialists. Thematic analysis, cross-group comparison, and narrative synthesis were applied. Findings reveal systematic and consistent COLREGs application errors concentrated in three domains: Rule 8 (Action to Avoid Collision) temporal decision-making, Rule 17 (Action by Stand-On Vessel) uncertainty management, and Rule 19 (Restricted Visibility) procedural sequence execution. A convergent expert-officer perception gap regarding the adequacy of current COLREG-focused simulation training provides the study's most practically significant cross-group finding. The study contributes a domain-specific diagnostic of COLREGs application competency gaps among Indonesian deck officers and provides institutionally actionable recommendations for Nautika curriculum enhancement at STIP Jakarta.